The Medical Perspective of Dry Cupping and Wet Cupping: Effects and mechanisms of action: The Medical Perspective of Dry Cupping and Wet Cupping - Fauzi Tanjung, Qadri; Ishadi, Hendi (Journal of Society Medicine, 2022)
This therapy is a method of cleaning the blood and wind by sucking. remove residual toxins in the body through the skin surface by sucking. Cupping is divided into two types, that’s wet cupping and dry cupping. Dry cupping includes slide cupping, fire cupping, and pull cupping. The difference between wet cupping and dry cupping is the presence or absence of blood. Cupping is an alternative method that involves placing a cup on the skin using heat or suction for a few minutes. This will pull the tissue under the skin and form a blood pool so that a localized healing process occurs. Cupping is very beneficial for these patients although the benefits may not be felt in the short term. The side effects caused by cupping are not severe, only cause discomfort due to cupped and incision on the skin. Cupping plays a role in reducing inflammatory mediators formed due to cell inflammation. This substance serves to send pain signals to the brain. Cupping can be used for diseases that are local or systemic. Cupping can be used to reduce pain such as headaches, carpal tunnel syndrome and some other local disease.